Bandwidth Management System for Academic Network at Khon Kaen University - Chaosakul, Arnut (Engineering and Applied Science Research, 2015)
There are many ways to resolve bandwidth insufficiency from unsanctioned application. Those methods are as follow: I. Increase bandwidth in both LAN side and WAN side. 2. Set up network policy for utilizing ban.dwidth according to an application behavior. 3. Install bandwidth management system for controlling bandwidth according to applications that are prioritized. Khon Kaen University (KKU) has implemented those three methods for bandwidth management, starting from method 2, method I and then method 3 repectively. By using network policy, this method is easy to implement and cost effective. After KKU has installed bandwidth’ management system, we found that a critical mission application has got a service guarantee by this system, not to be disturbed by low priority application.